Improvisational Dance-Based Psychological Training of College Students’ Dance Improvement - Dou, Xinyu; Jia, Lin; Ge, Jinchuan (Frontiers in Psychology, 2021)
Dance creation involves complex psychological activities. Although previous studies have conducted extensive investigations on the psychological aspects of choreographers’ creations, little is known regarding the psychological barrier of choreographers in terms of creativity. The study aims to explore the psychological barrier of innovation in dance choreography, which is a kind of situation between mental illness and mental problems. The research shows that improvisational dance is a free dance with the human body as a material carrier, and it is a dance form that the dancer’s thinking is transformed into dance action to express their inner thoughts. The improvement of the potential creative thinking of dance creators through the improvisational dance movement and structure are explored. Meanwhile, the theoretical ideas of psychologists have been applied to the cultivation and improvement of improvisational dance creativity, which has made full certification and supplement. Moreover, through psychological experiments, it is proved that improvisational dance is an important way to release and develop creativity. Based on the theory of psychology, feasible suggestions are given to improve students’ creative ability in the process of improvisational dance teaching.